Model of Hospital Infectious Waste Control in Padang City Based on Dynamic Systems - Elsa Yuniarti; Indang Dewata; Heldi Heldi; Mahalul Azam; Eri Barlian (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Padang City is the epicenter of the spread of COVID-19 in West Sumatra with the highest cases of COVID-19 as a result of which infectious waste in hospitals has increased. This study aims to build a model for controlling hospital infectious waste in Padang City based on a dynamic system, and formulate scenarios and policy recommendations for controlling hospital infectious waste in Padang City based on a dynamic system. This type of research is quantitative with a system dynamic approach. The research location is in Padang City from March 2020 – July 2022. Descriptive data is presented in the form of tables and graphs. Dynamic system modeling used Powersim Studio 10. The infectious waste control model for hospitals in Padang City based on the dynamic system of the COVID-19 pandemic case obtained simulation results from a population of 909,040 people in Padang City, there were 57.38% of the population exposed, 10.06% positive for COVID-19, 71.9% self-isolation, 28.1% hospitalized, and 1.27% death. Vaccination simulation obtained 85% vaccination 1, 69.69% vaccination 2, and 11.73% booster vaccination. From the hospital infectious waste simulation, there was an increase in the generation of infectious waste by 100% compared to before the pandemic. Model validity test obtained AME declared valid ( 10%) (4) Policy recommendations for controlling infectious waste in Padang City hospitals based on the dynamic system of the COVID-19 pandemic case are with the vaccination scenario, health protocols and PSBB will optimistically reduce positive COVID-19 cases, treatment and the generation of infectious waste in Padang City hospitals.